Zur liste der schwurgötter im Assur-Apûm-Vertrag - Kryszat, G. (ISIMU, 2016)
This article is a first try to deal with some of the questions as they are roused by a closer look at the list of the gods in the first lines of the Old Assyrian treaty between the City of Assur and the King of Apûm. Some aspects of the not immediately obvious changes that follow the reign of Šamši-Adad I shall be shown.